David Stern, Christoph Markschies, and Sarit Shalev-Eyni, Eds. The Monk’s Haggadah: A Fifteenth-Century Illuminated Codex from the Monastery of Tegernsee, with a Prologue by Friar Erhard von Pappenheim - Merback, Mitchell (Studies in Christian-Jewish Relations, 2016)
No abstract is available.